2009
DOI: 10.1007/s00424-009-0694-7
|View full text |Cite
|
Sign up to set email alerts
|

The glycocalyx maintains a cell surface pH nanoenvironment crucial for integrin-mediated migration of human melanoma cells

Abstract: The glycocalyx consists of proteoglycans, glycoproteins, glycosaminoglycans, associated plasma proteins, and soluble glycosaminoglycans and covers the surface of all eukaryotic cells. It mediates specific recognition events, modulates biological processes such as ligand-receptor interactions, and has been proposed to affect tumor metastasis. Here, we studied whether the glycocalyx is required for melanoma cell migration. We diminished the glycocalyx of human melanoma cells by inhibiting posttranslational N-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…These pH-environments are stabilized by the glycocalix (23). Particularly at focal adhesions at the cell front, the pericellular H + concentration is high.…”
Section: The Ecm Composition Arranges Motility and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pH-environments are stabilized by the glycocalix (23). Particularly at focal adhesions at the cell front, the pericellular H + concentration is high.…”
Section: The Ecm Composition Arranges Motility and Invasionmentioning
confidence: 99%
“…Both, adhesion to the ECM as well as its digestion require an optimum pH at the cell surface (22). In addition to the overall proton concentration present in the stroma, NHE1 activity represents a tunable proton source (15,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple integrins, such as a 2 b 1 , a 5 b 1 or a n b 3 , are pH-dependent in melanoma [19] and in other cells [66,67]. Increased adhesion at acidic extracellular pH values is explained by conformational changes that lead to an enhanced aviditity of the integrin headpieces to ECM proteins [67] or by a pH dependence of the mechanical stability of focal adhesions [68].…”
Section: Ionic Mechanisms Of Cell Migrationmentioning
confidence: 99%
“…Conceptually, it is important that integrins protrude only 20 nm into the extracellular space [69]. Therefore, it is not surprising that the pericellular pH e inside the glycocalyx is more important for cell adhesion than the pH of the extracellular bulk solution surrounding migrating melanoma cells [19,21]. The pericellular pH e even confers asymmetry upon migrating tumour cells, because it is more acidic at the cell front than at the rear end [21,28].…”
Section: Ionic Mechanisms Of Cell Migrationmentioning
confidence: 99%
“…His group found that the Na + /H + exchanger NHE1 is necessary for the migration of cultured human melanoma cells and acts through 1 integrin at the front of the cell to promote attachment to the substrate. This attachment is necessary for cell movement (Krahling et al, 2009). NHE1 is part of the focal adhesion contacts and accumulates at the cell front where its activity causes acidification at the cell surface.…”
Section: Introductionmentioning
confidence: 99%